Innovative methods and their advantages in teaching uzbek, russian and foreign languages - Ismoilova, Mahliyo (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article provides information on innovative methods that can be used in language learning for teachers and in the classroom, and their advantages. The article also contains practical recommendations developed by the author on the advantages of these methods.